The Anglosphere : a genealogy of a racialized identity in international relations - Vucetic, Srdjan, 1976- (Stanford, Calif. : Stanford University Press, 2011)
Focuses on Australia, Britain, Canada, New Zealand, and the United States.
What is the Anglosphere? -- Empire, Venezuela and the "great rapprochement" -- ANZUS, Britain and the "Pacific pact" -- Suez, Vietnam and the "great and powerful friends" -- Empire, Iraq and the "coalition of the willing" -- The Anglosphere identity and its limit.
Includes bibliographical references (p. 201-243) and index.
Keywords: Group identity -- Political aspects -- English-speaking countries; Security, International -- International cooperation -- Case studies; World politics -- 20th century; English-speaking countries -- Foreign relations